Teachers’ Perspective on Learning Based Digital Literacy - Indra Suhendra; Prana Dwija Iswara; Sartono Sartono (International Conference on Elementary Education, 2020)
Education continued to develop along with the development of the age, and this development affected the planning, process, even to the evaluation of learning. One of the developments was a technological development that continued to influence all aspects of life in the world including education. Therefore, teachers needed to understand the technology. The teachers must learn and understand digital literacy where this approach allowed to give great experiences in teaching. Of the 32 teachers as respondents, 84.4% knew digital literacy, and 15.6% did not know about it. However, the use of digital literacy in learning was still low